Medication adherence and community pharmacy: a review of education, policy and research in England - Clifford S; Garfield S; Eliasson L; Barber N (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Objective: The objective of this narrative review was to identify and describe the current policy, education and research related to community pharmacy and medication adherence in England.Methods: Medline, Embase, International Pharmaceutical Abstracts and Pharmline were used to search for relevant research articles. Current policy documents were identified via the websites of the Department of Health in England, the Royal Pharmaceutical Society of Great Britain, the National Pharmacy Association, the Pharmaceutical Services Negotiating Committee and NHS Employers. All pharmacy schools in England were contacted to obtain information about the adherence-related courses they provide to undergraduate and postgraduate pharmacy students.Results: National policies and guidelines in England are conducive to an increasing role for community pharmacists to support patients with medication adherence. Many pharmacy schools cover the issue of adherence in their undergraduate and postgraduate courses. Research in this area has tested the effectiveness of pharmacists providing adherence support in the form of compliance aids, education, involvement in discharge planning, and tailored interventions. Conclusion: In community pharmacy in England, current policy and funding arrangements suggest there is great scope for pharmacists to support patients with medication adherence. Further research is necessary to identify the most useful, cost-effective and sustainable approach in practice.